Electroacupuncture ameliorates post-traumatic stress disorder in rats via a mechanism involving the BDNF-TrkB signaling pathway - Li, Mi; Xie, Yiqiang; Niu, Kun; Li, Kai (Cellular and Molecular Biology, 2020)
Post-traumatic stress disorder (PTSD) is a mental health condition triggered by a terrifying event, causing flashbacks, nightmares and severe anxiety. It develops in individuals who have experienced a shocking, scary, or dangerous event. Electroacupuncture is reported to be effective for the treatment of PTSD. The present study was carried out to investigate the protective effect of electroacupuncture in a rat model of PTSD, and the mechanism involved. Specific-pathogen-free male Sprague Dawley rats (n = 30) weighing 180 – 220 g (mean weight = 200 ± 20 g) were randomly assigned to three groups of ten rats each: control group, single-prolonged stress (SPS) group, and treatment group. The treatment group rats received electroacupuncture. Changes in PTSD-like behavior were assessed using locomotor activity, elevated plus-maze (EPM) and fear conditioning tests. The mRNA and protein expressions of brain-derived neurotrophic factor (BDNF) and tropomyosin receptor kinase B (TrkB) were determined using real-time quantitative polymerase chain reaction (qRT-PCR) and Western blotting, respectively. Co-immunoprecipitation (Co-IP) was used to measure BDNF and TrkB binding interaction, while chromatin immunoprecipitation (ChIP) was used to evaluate the binding between cyclic adenosine monophosphate (cAMP) response element-binding protein (CREB) and its target genes. Electroacupuncture significantly increased locomotor activity and exploratory behavior, but significantly reduced general fear and anxiety in SPS rats (p < 0.05). It also significantly upregulated the mRNA and protein expressions of BDNF and TrkB, and increased the binding of BDNF to its receptor TrkB (p < 0.05). Electroacupuncture significantly increased the binding of CREB to BDNF promoter region (p < 0.05). Electroacupuncture ameliorates PTSD in rats via a mechanism involving the BDNF-TrkB signaling pathway.